Influence of Hydrothermal and Pyrolysis Processes on the Transformation of Organic Matter of Dense Low-Permeability Rocks from Domanic Formations of the Romashkino Oil Field - Galina P. Kayukova; Anastasiya N. Mikhailova; Nailia M. Khasanova; Vladimir P. Morozov; Alexey V. Vakhin; Nafis A. Nazimov; Oleg S. Sotnikov; Rais S. Khisamov (Geofluids)
The model experiments regarding the conversion of organic matters from carbonate rock samples of Dankov-Lebedyan deposits of Zelenogorskaya area and siliceous-carbonate rocks of Semiluki-Mendym deposits of Berezovskaya area of Domanic formations of Romashkino oil field were carried out. Two types of experiments were carried out: (1) the hydrothermal treatment of rocks at a temperature of 350°C in the presence of carbonic acid and a water content of 30%; (2) pyrolysis at temperatures of 350 and 600°C in the presence of hydrogen. The yield and quality of extracted hydrocarbons from the rocks depending on the mineral composition of rocks, content and composition of organic matter, and thermal stability of kerogen under hydrothermal influences were evaluated. Application of electron paramagnetic resonance in pyrolysis processes revealed the difference in mineral content of rocks (Mn2+, SO3−, and SO2− ions) and free radicals R∗, as well as in vanadyl ion (VO2+) concentration. It is established that an increasing temperature of pyrolysis promotes the formation of new free organic radicals in rock samples: in Domanic rocks of Semiluki-Mendym deposits at 350°С and in carbonate rocks of Dankov-Lebedyan horizon at 600°С. This indicates different ability of oil-generating potential of rocks with hydrothermal and pyrolysis technologies.